EFEITOS ERGOGÊNICOS DA MÚSICA NAS AULAS COLETIVAS DE JUMP - Perfeito, Rodrigo Silva; Matos, Stefannie da Silva; Fonseca, Ãlax Alves da (International Journal of Movement Science and Rehabilitation, 2021)
This study aims to investigate the influence of music as an ergogenic resource in the collective classes of Jump in the gyms. To this end, it reported a sample of 22 healthy individuals, practitioners of physical exercises who participated in activities in which a song was used as one of the main elements of the class. To analyze the efforts, heart rate (HR) and effort perception (E.BORG) were collected in music classes (CM) and without music (SM). The taxes concluded two sessions (CM and SM), divided into three stages: metronome 120, metronome 140 and metronome 160 with continuous execution on the mini trampoline. As a mean of HR and E.BORG values, there was a gradual difference in intensity increase and a perceived exertion in the CM group. Conclude that a song is an efficient ergogenic resource for jump practitioners as it allows you to decrease the perception of effort and increase the intensity at different motor rhythms.